A curriculum transformation strategy: Building AACN competencies into end-of-semester report-out. - Davis, Rebecca G.; Gentry, Sheila (Journal of Professional Nursing, 2026)
A successful transition to competency-based education in nursing requires faculty engagement along with structured processes for implementation and evaluation. This article describes the integration of competency-based teaching and assessment strategies into the end-of-semester report-out process used in the four tracks of a Bachelor of Science in Nursing program. Initially designed to strengthen curriculum by facilitating communication of learner outcomes, end-of-semester report-out was further expanded to engage and support faculty in course-level integration of The Essentials: Core Competencies for Professional Nursing Education. Faculty discussed experiences aligning course assignments with relevant sub-competencies, revising grading rubrics, and implementing competency-based clinical assignments and evaluations. The report-out format encouraged shared ownership of curriculum development, provided consistent data for ongoing program evaluation, and fostered faculty reflection on teaching practices. Outcomes from the enhanced report-out process have included creation of learner-centered teaching strategies, improved assessment of learner competency across clinical and didactic experiences, and collection of meaningful data for program assessment and accreditation. Structured, faculty-driven processes, such as end-of-semester report-out, may promote sustainable curricular change and continuous improvement in competency-based nursing education. • End-of-semester report-out supports faculty collaboration when evalutating AACN Essentials implementation and CBE efforts. • Report-out discusses teaching innovations, diverse evaluation strategies, and reflection on course outcomes and experiences. • Report-out supports faculty engagement and shared governance in transitioning to competency-based education.